2013
DOI: 10.5296/ijafr.v3i1.3803
|View full text |Cite
|
Sign up to set email alerts
|

Relative Ability of Earnings Data and Cash Flow in Predicting Future Cash Flows

Abstract: The purpose of this study is to examine earnings relative ability, operational cash flow, and two traditional measures of cash flows namely net earnings plus depreciation and operational working capital in predicting future cash flows. Also, the effect of company size on ability of predictive measures mentioned is examined in this study. The population examined includes accepted companies in Tehran Stock Exchange during period from 2005 to 2009. The results indicate that net earnings have more ability than ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Working capital is valued as the company's ability to finance the company's operations by using capital owned by the company without funding from other parties. This research model uses the research model of Takhtaei and Karimi (2013) namely:…”
Section: Accrual Componentmentioning
confidence: 99%
“…Working capital is valued as the company's ability to finance the company's operations by using capital owned by the company without funding from other parties. This research model uses the research model of Takhtaei and Karimi (2013) namely:…”
Section: Accrual Componentmentioning
confidence: 99%
“…They play an essential role in managing debt and debt contracts and alone have a high capacity for predicting potential cash flows (Atqa et al, 2019). In a similar vein, Takhtaei and Karimi (2013) have found that net earnings have a better capacity than operational cash flows and conventional proxies for anticipating future cash flows. Since 1978, the Financial Accounting Standard Board (FASB) has mentioned estimating operating cash flows, emphasising that historical earnings interest investors more than historical cash flows for predicting potential cash flows (Nguyen & Nguyen, 2020).…”
Section: Historical Earnings and Future Cash Flowmentioning
confidence: 89%
“…Research that examines the effect of operating flow on stock returns which has no significant effect is the same as the research conducted by Takhtaei [13] because the highest and lowest values are between cash flow and stock returns in different companies. In terms of the effect of investment cash flow on stock returns, which has an insignificant effect in line with research conducted, Darmayanti [14] does not affect investment cash flow on the value of stock returns in manufacturing companies for the 2016-2018 period, an assessment of the average value of investment cash flows and stock returns that are not in sync.…”
Section: Effect Together (Silmutan)mentioning
confidence: 99%